The Return of Prejudice in Europe's Regions: The Moderated Relationship between Group Threat and Economic Vulnerability. Issue 3 (2nd July 2016) - Isaksen, Joachim V.; Jakobsen, Tor G.; Filindra, Alexandra; Strabac, Zan
Abstract : Using data from 16 countries and employing multilevel analysis that encompasses the national, regional, and individual levels, we find that both economic and social factors trigger anti-immigrant attitudes among Europeans. Regional per capita GDP is positively correlated with tolerant attitudes while the regional unemployment rate drives prejudice. We find a moderating relationship between immigrant population size and per capita GDP, which suggests that, as the size of the immigrant population increases, prejudice rises but only in poorer regions. In more affluent regions, an increase in the immigrant population corresponds to increased tolerance.